The Effect of Giving Red Dragon Fruit Juice on Changes in Leukocyte Levels and Fatigue Time in Maximum Intensity Physical Exercise - Rianingsih, Rika; Rusip, Gusbakti (Buletin Farmatera, 2021)
Physical exercises contribute to oxidative tresses to cause fatigue and reduce the level of antioxidants in the body so that it affects physical fitness. Antioxidants are needed to neutralize free radicals and prevent damage to oxidative stress. This study aimed to determine the effect of red dragon fruit juice (Hylocereus polyrhizus) on leukocyte levels and tiring time in maximum intensity physical exercise. This research is the experimental research of the pre-test and post-test control group design. The research samples were divided into two groups, i.e. the control and treatment groups. Leukocyte levels were checked by using 2ml blood samples with hematology analyzers. Tiring time was determined by a treadmill test, in which the subject was asked to run until he/she reached maximum pulse. The minute the subject feels fatigued was documented as tiring time. This study showed significant results of leukocyte levels before and after treatment with a p-value of 0.005, tired time showed a p-value of 0.001, in which there was the lateness of tired time among the intervention group. Subjects who were given red dragon juice showed there was no increase in leukocyte levels and experienced lateness in the occurrence of tired time. That showed a better physical fitness level among the intervention group.